Acquiring allophonic structure and phonetic detail in a bilingual community: The production of laterals by Sylheti-English bilingual children. (June 2021) - Kirkham, Sam; McCarthy, Kathleen M.
Aims and objectives: In this study, we consider the acquisition of allophonic contrast and phonetic detail in lateral consonants by second-generation Sylheti-English bilingual children in London, UK. Design/methodology/approach: Acoustic analysis was conducted on productions of /l/ by Sylheti bilingual children, Sylheti monolingual adults and English monolingual children. Data and analysis: Tokens of /l/ were elicited across initial, medial and final word positions from 14 bilingual Sylheti-English children, 10 monolingual English children, and 4 monolingual Sylheti adults. Acoustic measurements of F2–F1 were analysed using Bayesian linear mixed-effects modelling. Findings and conclusions: Our results show that bilingual children produce monolingual-like positional patterns in Sylheti, with very clear laterals in all positions. In contrast, bilinguals produce monolingual-like positional allophony in English, but they differ in phonetic detail, with bilinguals producing much clearer laterals than monolingual children across all positions. Originality: This study is the first to examine the development of allophonic contrast and phonetic detail in both of a bilingual's languages in a contact scenario. This provides new insights into how contact varieties adopt aspects of structure and detail from each language. We also report valuable data from Sylheti-English bilinguals, who are an understudied community. Significance/limitations: Our study highlights the value of considering structural and detailed aspects of cross-linguistic sound systems, whereby one aspect may show monolingual-like patterns and another aspect may show distinctive patterns. We propose that the results in this study represent the development of a new sound system out of language contact, with second-generation bilingual children producing a hybrid system that combines influences from both heritage and host languages.